Photothermal 2D Nanosheets Combined With Astragaloside IV for Antibacterial Properties and Promoting Angiogenesis to Treat Infected Wounds - Liu, Lichang; Wang, Wenfeng; Hong, Weihong; Jin, Yuyan; Wang, Lichun; Liu, Sujun; Wang, Ailin; Liu, Xusheng (Frontiers in Bioengineering and Biotechnology, 2022)
Bacterial infection, inflammatory disorder and poor angiogenesis of tissue in chronic wounds are main reasons causing wound difficult to heal. In this study, a novel MSN-PEG@AS/BP nano-spray was designed to solve these issues. Astragaloside IV (AS) were load in mesoporous silica nanoparticles (MSN) to enhance angiogenesis and controlregulate inflammation, and the two-dimension (2D) nanosheet black phosphorus (BP) was used for bacterial killing through photothermal effect. Under the thermal decomposition, the covalent bond of polyethylene glycol (PEG) was broken, releasing AS to promote the proliferation of fibroblasts, the formation of blood vessels and the resolution of inflammation. AS can promote the polarization of the anti-inflammatory (M2) macrophage phenotype to enhance the deposition of extracellular matrix and the formation of blood vessels. Besides, BP showed significant photothermal effect and nearly 99.58% of E. coli and 99.13% of S. aureus were killed in antibacterial study. This nano-spray would be a novel therapeutic agent for infected wound treatment.